Stoibocephalum n. gen. (Cestoda: Lecanicephalidea) from the sharkray, Rhina ancylostoma Bloch & Schneider (Elasmobranchii: Rhinopristiformes), from northern Australia - Cielocha, Joanna J.; Jensen, Kirsten (Zootaxa, 2013)
A new genus and species of lecanicephalidean cestode, Stoibocephalum arafurense n. gen., n. sp., is described from the sharkray, Rhina ancylostoma Bloch & Schneider, off northern Australia. Stoibocephalum arafurense n. gen., n. sp. Is apolytic, and possesses a large, muscular, retractable apical organ, 3 pairs of excretory vessels, and testes in several columns and layers. The presence of 3 pairs of excretory vessels distinguishes this new genus from all other valid lecanicephalidean genera, except Hexacanalis Perrenoud, 1931, from which it can be distinguished based on ovary shape and egg morphology. Stoibocephalum n. gen. most closely resembles Tylocephalum Linton, 1890 but differs from that genus in its ability to completely retract its apical organ into the scolex proper. Scolex microthrix pattern and histological sections of scoleces attached in situ suggest S. arafurense n. gen., n. sp. to attach to the host’s intestinal mucosa with apical organ and scolex proper surfaces, rather than just the apical organ surface. This is the third lecanicephalidean species described from the sharkray.